What value can cultural policy have for the future of television broadcasting in South Africa? The application of Shalini Venturelli's policy challenges for the creative economy to the future of South African television content - Reddy, Trisan (My University, 2009)
Abstract This research report considers the use of cultural policy in the broadcasting industry. It looks at the applicability of the policy recommendations made by Shalini Venturelli for cultural policy in the information economy. A brief look at the debates encompassing the use of cultural policy and the history of South African broadcasting is provided. Scenario planning and interviews are used as methodological tools to assist in the analysis of the topic. This report concludes that Venturelli's suggestions are indeed relevant and that a policy framework that is more facilitative, as cultural policy is, rather than regulatory, as present South African broadcasting legislation is, is needed for the future growth of the industry.